2012
DOI: 10.21273/jashs.137.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters and Development of a Selection Index for Breeding Red Raspberries for Processing

Abstract: New commercial red raspberry (Rubus idaeus) cultivars suited to machine-harvesting and processing markets need to be high-yielding and have good fruit quality attributes, including fruit firmness, sugar content, acidity, flavor, and health properties. Combining many traits in one genotype is a challenge for breeders, especially for traits negatively correlated with yield. Despite its potential, the use of multiple-trait selection through selection indices has had limited appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Previous studies indicate that anthocyanin accumulation in red raspberry is primarily under genetic control, with some variation due to environmental factors (Anttonen and Karjalainen, 2005;Conner et al, 2005;Freeman et al, 2011;Kassim et al, 2009;Ozgen et al, 2008;Stephens et al, 2012). Consistent with these reports, the majority of differences in anthocyanin content or individual anthocyanins were found among cultivars in our study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies indicate that anthocyanin accumulation in red raspberry is primarily under genetic control, with some variation due to environmental factors (Anttonen and Karjalainen, 2005;Conner et al, 2005;Freeman et al, 2011;Kassim et al, 2009;Ozgen et al, 2008;Stephens et al, 2012). Consistent with these reports, the majority of differences in anthocyanin content or individual anthocyanins were found among cultivars in our study.…”
Section: Resultssupporting
confidence: 91%
“…Ellagitannin content did not differ significantly between tunnel and field-cultivated samples. Stephens et al (2012) found ellagitannins in red raspberry to have moderate narrow-sense heritability estimates (h 2 = 0.46), and genotype • year correlations (r GY = 0.67), indicating that ellagitannin levels are primarily under genetic control. There was a cultivar • location interaction for Sanguiin H-6 content (P = 0.0094).…”
Section: Resultsmentioning
confidence: 94%
“…This indicated that different environmental conditions for both years likely affected firmness and this was reflected in all three types of firmness measurements. As in other fruits, such as apple and red raspberry (Rubus idaeus L.), firmness is a quantitative trait that is challenging to improve (Clark, 2005;Iwanami et al, 2008;Stephens et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The fruit size, expressed by its weight (FW), is a relevant commercial trait as yield and quality component (Bautista et al, 2017;Stephens et al, 2012a). This study revealed that 58% of FW expression is due to genetic effects, similarly to Bautista et al (2017) and González (2016), who observed moderate narrow sense heritability, ĥ 2 =0.48 and ĥ 2 =0.52, respectively, for this trait in raspberry.…”
Section: Discussionmentioning
confidence: 51%
“…The main objectives in the breeding programs for raspberries are related to high fruit quality, morphological traits, yield, suitability for market and machine harvesting, environmental adaptation, and pest and disease tolerance or resistance (Stephens et al, 2012a;Gambardella et al, 2016;Jennings et al, 2016;Moore et al, 2016;Orzel et al, 2016). Another breeding goal is to improve the content of phytochemical compounds such as anthocyanin, phenolic compounds, and soluble solids (Milivojevic et al, 2011;Stephens et al, 2012a;Orzel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%